Ticagrelor vs. Clopidogrel After Complex Percutaneous Coronary Intervention in Patients With Stable Coronary Artery Disease - Xi, Ziwei; Li, Jianan; Qiu, Hong; Guo, Tingting; Wang, Yong; Li, Yang; Zheng, Jianfeng; Dou, Kefei; Xu, Bo; Wu, Yongjian; Qiao, Shubin; Yang, Weixian; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Patients undergoing complex percutaneous coronary intervention (PCI) have an increased risk of cardiovascular events. Whether potent antiplatelet therapy after complex PCI improves outcomes in patients with stable coronary artery disease (SCAD) remains unclear. Objectives: To assess the efficacy and safety of ticagrelor versus clopidogrel in patients with SCAD undergoing complex PCI. Methods: Patients with a diagnosis of SCAD and undergoing PCI during January 2016 to December 2018 were selected from an institutional registry. The primary efficacy endpoint was major adverse cardiac events (MACE) within 12 months after PCI. The primary safety endpoint was major bleeding. Results: Among 15459 patients with SCAD included in this analysis, complex PCI was performed in 6335 (41.0%) patients. Of patients undergoing complex PCI, 1123 patients (17.7%) were treated with ticagrelor. The primary efficacy outcome after complex PCI occurred in 8.6% of patients in the ticagrelor group and 11.2% in the clopidogrel group. Compared to clopidogrel, ticagrelor decreased the risk of MACE in patients undergoing complex PCI (adjusted hazard ratio [HR]: 0.764; 95% confidence interval [CI]: 0.615 to 0.949; p=0.015), but not in noncomplex PCI (p for interaction=0.001). There was no significant difference in incidence of major bleeding between patients treated with ticagrelor and clopidogrel (p=0.221), while ticagrelor was associated with an increased risk of minor bleeding (adjusted HR: 3.099; 95% CI: 2.049 to 4.687; p<0.001). Conclusion: In patients with SCAD and undergoing complex PCI, ticagrelor could substantially reduce the risk of adverse cardiovascular outcomes without increasing the risk of major bleeding compared with clopidogrel.